Mechanism of current flow and temperature dependence of contact resistivity in Au-Pd-Ti-Pd-n⁺ -GaN ohmic contacts - Sachenko, A.V.; Belyaev, A.E.; Boltovets, N.S.; Kapitanchuk, L.M.; Klad’ko, V.P.; Konakova, R.V.; Kuchuk, A.V.; Korostinskay, T.V.; Pilipchuk, A.S.; Sheremet, V.N.; Mazur, Yu.I.; Ware, M.E.; et al. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
We present the results of structural and morphological investigations of
interactions between phases in the layers of Au-Pd-Ti-Pd-n⁺-GaN contact metallization that appear at rapid thermal annealing (RTA). It is shown that formation of ohmic contact
occurs in the course of RTA at Т = 900°C due to formation of titanium nitride. We
studied experimentally and explained theoretically the temperature dependence of
contact resistivity ρс(Т) of ohmic contacts in the 4.2-380 K temperature range. The ρс(Т)
curve was shown to flatten out in the 4.2-50 K range. As temperature grew, ρс decreased
exponentially. The results obtained enabled us to conclude that current flow has field
nature at saturation of ρс(Т) and the thermofield nature in the exponential part of ρс(Т)
curve.